Influence of Turbulence, Orientation, and Site Configuration on the Response of Buildings to Extreme Wind - Aly Mousaad Aly (The Scientific World Journal)
Atmospheric turbulence results from the vertical movement of air, together with flow disturbances around surface obstacles which make low- and moderate-level winds extremely irregular. Recent advancements in wind engineering have led to the construction of new facilities for testing residential homes at relatively high Reynolds numbers. However, the generation of a fully developed turbulence in these facilities is challenging. The author proposed techniques for the testing of residential buildings and architectural features in flows that lack fully developed turbulence. While these methods are effective for small structures, the extension of the approach for large and flexible structures is not possible yet. The purpose of this study is to investigate the role of turbulence in the response of tall buildings to extreme winds. In addition, the paper presents a detailed analysis to investigate the influence of upstream terrain conditions, wind direction angle (orientation), and the interference effect from the surrounding on the response of high-rise buildings. The methodology presented can be followed to help decision makers to choose among innovative solutions like aerodynamic mitigation, structural member size adjustment, and/or damping enhancement, with an objective to improve the resiliency and the serviceability of buildings.